Lightweight Reprogramming and Energy Balancing in Wireless Sensor Networks - Dinh-Sy Do; Younghan Kim (International Journal of Distributed Sensor Networks)
Reprogramming in wireless sensor networks is important and challenged by the dynamic environment and its own characteristic, frequently sleeping. Although there has existed various approaches, they still suffer from message control redundancy and energy balancing issues. In this paper, we consider the problem of lightweight code distribution and energy balancing in wireless sensor networks by utilizing shared requests to reduce redundant control messages. Additionally, our contribution is enhanced by various solutions, such as multisegment advertisement strategy and edge-oriented strategy. Through analysis and evaluation sections, we confirm that our protocol does not only help to reduce update completion time by 1/3 compared with the Deluge protocol, but also significantly decreases redundant control messages and balances energy consumption among nodes in the updating process.